Caracterização física, balanço de massa e avaliação de critérios de projeto da unidade de decantação da estação de tratamento de efluentes de refinaria de alumina - OLIVEIRA, Elaine Cristina dos Santos Cunha de (Universidade Federal do Pará, 2024)
The research aimed to evaluate the physical aspects of the liquid phase and the solid phase, as well as to evaluate the performance of the decanters of an ETEI, located in Barcarena, through the mass balance and comparison of the TAH and the solids application rate (TAS). with project references and standards. Two of the four lines of ETEI decanters under study were monitored, on two consecutive days samples were collected from the liquid phase at the inlet and outlet, and from the solid phase, the ETEI sludge. The analyzes were carried out at the Laboratory of the Federal University of Pará (LAESA), together with the solids analyses, flow data was consulted using online monitoring instruments, as well as project data in technical files and a survey of normative and bibliographical references. With the results obtained, it was possible to conclude that the concentration of total solids is higher in Decanter 82E when compared to Decanter 82C. The result of the solids analysis also made it possible to evaluate the higher percentage in the portion of fixed suspended solids, that is, indicating a higher inorganic load characteristic. Regarding the mass balance, a generation of solids inside the decanters is observed due to the fact inherent to the process which refers to the presence of caustic soda in the raw effluent, aligned with the neutralization reaction that occurs in the medium through the use of sulfuric acid, forming sodium sulfate as a by-product of the treatment process, therefore this increase in solids is expressed in terms of dissolved solids. Regarding the assessment of the TAH observed in the monitored data, it was higher than the minimum indicated by Metcalf & Eddy (1991), but it remained in line with the design reference, compatible with the behavior of flows at low load. And in this same comparative logic, the TAS evaluation remained in both decanter 82C and 82E at a rate lower than the minimum indicated by Metcalf & Eddy (1991)